Development of Assessment Model on Green Ergonomic Building for Office Building - Bintang Nidia Kusuma (School of Industrial and System Engineering, Telkom University, 2023)
World economic growth is directly proportional to the increase in the building sector. The building sectoraccounts for 31% of global energy consumption. Humans also increasingly recognize the importance of thehealth aspects, convenience indoor quality, and user safety in the building. This study combines theconcepts of green building assessment and green ergonomics to produce a new framework called greenergonomic building. The green ergonomic building is a building condition that not only focuses on energyuse, indoor quality but also health, convenience, safety, and improving quality of human life in carryingout their activities in buildings. The development of a green ergonomics building assessment model wasdeveloped from literature studies and questionnaires distributed to respondents working in green buildingcertified office buildings. Data processing using the Principal Component Analysis. The results of dataprocessing, seven dimensions of proposals and indicators are obtained. These dimensions are the basiccomponents of indoor quality and security; waste management and safety; water efficiency managementand artificial lighting; suitability of furniture work area and material; application of sensory technologiesand health; the convenience of workspace; and mechanical ventilation and supporting facilities. Thesedimensions and their indicators are expected to be used as a valuation model to identify that buildings havemet the green ergonomic building assessment requirement.